The Importance of Teacher Professionalism in Facing The Industrial Revolution Era 4.0 - Sari, Indah Novita; Vonna, Cut Nurul Zara; Retnoningrum, Fenti (Universitas Sebelas Maret, 2019)
This article aims to exlain the importance of developing teacher professionalism in facing the era of the industrial revolution 4.0. The research method used is the study of literature. Data collection is carried out by conducting a study of books, literature, notes and reports that have to do with the importance of teacher professionalism in facing the industrial revolution era 4.0. so in this article includes general processes such as: systematically identifying the theory, library discovery, and analysis of documents that contain information related to the research topic. The results of this study are in the form of a description related to development that can be dont by teachers to develop teacher professionalism in facing the era of the industrial revolution 4.0 well.